A meta-analysis of physical activity interventions in people with physical disabilities: Content, characteristics, and effects on behaviour. (July 2018) - Ma, Jasmin K.; Martin Ginis, Kathleen A.
Abstract: Objectives: Among samples of people with physical disabilities, the effects of physical activity (PA) interventions and the factors that influence intervention success are unknown. The purpose of this meta-analysis was to i) evaluate the overall effect of interventions on PA behaviour and ii) examine the influence of intervention characteristics, theory, and behaviour change techniques (BCTs) on PA intervention effects in persons with physical disability. Design: Meta-analysis. Method: Medline, Embase, PsychINFO, and AMED databases were searched for randomized controlled trials that evaluated the effects of a PA intervention in people with physical disability. Data were extracted regarding study and intervention characteristics and use of theory. Intervention descriptions were coded using the BCT Taxonomy version 1. Results: A total of 24 articles met the inclusion criteria. Overall, interventions had a small to medium-sized effect on PA behaviour ( g  = 0.35, k = 22, 95% CI [0.21, 0.48]). Interventions that used theory ( g  = 0.53, k  = 12, 95% CI [0.38, 0.68]) had larger effects than interventions that did not, p  < 0.001. Interventions that included self-monitoring of behaviour produced larger effects ( g  = 0.45 k  = 12, 95% CI [0.28, 0.63], p  = .04) and interventions with monitoring of behaviour by others without feedback produced smaller effects ( g  = 0.05, k  = 3, 95% CI [-0.22, 0.32], p  = .02) than studies without these BCTs. Conclusion: Interventions to increase PA behaviour in people with physical disability are effective, especially when theory is used to guide their development. Research is needed to examine a wider range of BCTs and the moderating effects of intervention characteristics on PA behaviour. Highlights: Overall, physical activity interventions showed small to medium-sized effects on physical activity behaviour (g = .35). Larger effects were yielded when intervention development was guided by behaviour change theory. Interventions incorporating self-monitoring had larger effects on physical activity behaviour than those that did not. Interventions using monitoring of behaviour by others without feedback had smaller effects on physical activity behaviour.